2022
DOI: 10.1177/1942602x221079758
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Adolescent Mental Health: Sounding the Alarm

Abstract: Adolescence is a period of emotional and developmental vulnerability in which mental illness can be first detected. This is also a time in which adolescents are introduced to social media and may experience the direct and indirect criticism that accompanies it. School nurses are providers that may be the first to detect signs and symptoms of adolescent mental illness inside and outside of the classroom. In order to decrease the risk of social media’s harmful effects, school nurses should consider providing ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Although IA is not considered a disorder in diagnostic and statistical manual of mental disorders, there is evidence that digital technology can be addictive and cause maladaptive mental health consequences in susceptible individuals (10). A number of studies have reported impaired sleep quality as a result of IA (9,(11)(12)(13). Sleep is a basic need and Cognitive skills, learning and emotional regulation are damaged with poor sleep quality (14).…”
Section: Introductionmentioning
confidence: 99%
“…Although IA is not considered a disorder in diagnostic and statistical manual of mental disorders, there is evidence that digital technology can be addictive and cause maladaptive mental health consequences in susceptible individuals (10). A number of studies have reported impaired sleep quality as a result of IA (9,(11)(12)(13). Sleep is a basic need and Cognitive skills, learning and emotional regulation are damaged with poor sleep quality (14).…”
Section: Introductionmentioning
confidence: 99%